Development of Printability of Bio-Composite Materials Using Luffa cylindrica Fiber - SÖNMEZ, SİNAN (NORTH CAROLINA STATE UNIV DEPT WOOD & PAPER SCI, 2016)
This study examined the surface adhesion of ink on bio-composite materials that were produced using Luffa cylindrica fiber and epoxy. To increase the ink adhesion on the surface, two different production methods were developed. The surface roughness and the surface contact angle of the bio-composite surfaces manufactured by each method were determined. The printing was applied on the surface of the bio-composite materials using a screen-printing procedure. While keeping the printing conditions constant, two different ink types, environmentally friendly water-based ink and solvent-based ink, were utilized. As a result of this study, the two types of ink were adhered on the polymer-coated surface, and there was no adhesion on the uncoated surfaces. In addition, the printability of the solvent-based ink was better than the water-based one, and the image of the transfer had higher quality. When the water or solvent-based inks were applied on the surface, the groups capable of forming hydrogen bonds, which were present in both kinds of ink, constituted hydrogen bonds with the C=O and N-H groups. This resulted in better adhesion on the surface, which was due to the presence of the separator.
Keywords: Luffa cylindrica fiber; Bio-composite; Printability; Polymer coating; Ink; GLOSS; ROUGHNESS; POLYMERS